HAPPINESS AND THE METAPHYSICS OF AFFECT - Haybron, Daniel (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique (CRÉ), 2022)
This paper introduces a category of functional conditions to address certain difficulties that have arisen in philosophical work on the nature of happiness. In earlier work, I defended an emotional state theory of happiness on which being happy consists substantially in dispositional states, such as one’s propensity for a relaxed or cheerful mood. Hedonistic accounts of happiness, which reduce it to experiences of pleasure, were rejected partly on the grounds that they appear to commit a category mistake. However, the nature of this category mistake remained unclear, and the claimed dispositionality of happiness has likewise been challenged even by commentators otherwise sympathetic with an emotional state theory. Here I address these worries by sharpening the metaphysical underpinnings of the emotional state view as I have articulated it. Understanding happiness in terms of an individual’s functional condition resolves these puzzles in a way that helps to explain the distinctive significance of happiness.